PENGARUH BRAND AWARENESS TERHADAP PURCHASE-INTENTION DIMEDIASI OLEH PERCEIVED-QUALITY DAN-BRAND-LOYALTY - Eliasari, Putu Ratih Arta; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
ABSTRACT   The purpose of this study was conducted to determine the effect of brand awareness to purchase intention mediated by perceived quality and brand loyalty. This research was conducted at drinking water industry of Kaori Brand in Denpasar with the sample size used by 80 respondents based on the questionnaire method. Data collection was obtained from questionnaires using Likert scale which was used to measure 16 indicators based on PLS analysis method. Based on the results found that brand awareness has a positive and significant impact on purchase intention and brand loyalty. Brand loyalty has a positive and significant impact on purchase intention. Brand awareness has a positive and significant effect on perceived quality. Perceived quality has a positive and significant impact on brand loyalty and purchase intention. Brand loyalty is able to mediate perceive quality against purchase intention. And perceived quality is able to mediate brand awareness to purchase intention.   Keywords : brand awareness, brand loyalty, perceived quality, purchase intention